A Biomechanical Investigation into Force, Power and Bone Morphology - Nicholas J. Owen (2018)
Force (F), produced by the neuromuscular system and transmitted by bones, is necessary for locomotion. Performance in activities of daily living and sport requires effective production and use of (F) for optimal outcomes. Quantifying neuromuscular performance, with F and force derived variables, allows monitoring of the effectiveness of training. Strength (S), power (P) and rate of force development (RFD) are important neuromuscular variables (NV) for predicting physical performance, which can be measured using a force platform (FP). This corpus comprises of 5 papers that examine different aspects of force in terms of human performance. Paper 1, investigated using postactivation potentiation (PAP), that may increase P temporarily, on international swimmers and the effect on start time compared to a traditional warm-up. There was no difference in start time although P was enhanced. PAP could be a useful alternative to a traditional warm-up. Paper 2, examined the relationship between isometric F variables and dynamic performance using new method of F analysis. Correlations were found between RFD, peak F and F at 100 ms vs.10 m sprint times and jump height. Paper 3, reported the first published criterion method for determining peak mechanical P (Pp) in a countermovement jump (CMJ), measured by a FP, with an accuracy < 1%. Paper 4, reported Pp normative values, which could be used to measure coordination and bone health in children, 7 to 11 years old, as existing, subjective measures are unreliable. Athletes’ bones experience high forces, causing changes in their shape and composition. The Mary Rose skeletal collection comprises of 97 skeletons, some of which were elite athletes (archers). Paper 5 reports a valid and reliable method measuring periosteal cross sectional areas to accuracies of < 1% essential for identification of occupational activity and bone health measurement. NVs are useful metrics for assessing human performance and bone health. Morphometrics of bone health and NVs need to be optimised for validity and reliability in order to derive maximum performance and clinical benefit.